Spatial Analysis of Surface Characteristics in the Western Basins of Al-Muthanna Desert - Naseh Hussein, Researcher. Aqeel; Abdullah Rahim, Prof. Dr. Najm; Shaker Maatouq, Prof. Dr. Safia (Basra studies journal, 2026)
This paper examines the western basins of Al-Muthanna desert as one of the important dry basins in the southern Iraqi desert. The study of the topographical characteristics of these basins reflects the interrelationships between erosion factors and processes, in combination with the associated and resulting geological phenomena. This analysis relies on data obtained from contour maps and satellite imagery. The field study of the region and digital elevation data (DEM) were used to create a geographic database of the region's basins, due to the importance of the valley basins and the possibility of rehabilitating them. The study also aimed to provide results and proposals based on the results of the geomorphological characteristics of the basins of the western Al-Muthanna desert, which cover an area of ​​(42,382) km2, and are located in the north eastern part of the south western desert of Iraq within the administrative boundaries. Al-Muthanna Governorate is considered a dry basin for most of the year, with water flowing only during the rainy season. The features of its valleys and river network were shaped under rainy conditions dating back to the Pleistocene era. Analysis of the basin's surface characteristics and their impact on geomorphological processes reveals increased activity in slope retreat and landslide processes in the region has contributed to the development of erosive activity in the basins and variations in surface characteristics